(untitled) (Global Journal of Medical Research, 2014)
Disseminated cysticercosis is a rare complication characterized by extensive dissemination of larvae (Cysticercus cellulosae) of Taenia solium throughout the human body involving brain, subcutaneous tissue, skeletal muscles and other organs. The symptoms depend upon the parasite burden, its location, stage of cyst evolution and host immunity. We report a case of immunocompetent 47-year-old alcoholic male who presented with symptoms of chronic liver disease. Disseminated cysticercosis was an incidental finding. The emphasis is on the presence of calcified cysticerci in portal and splenic vein thrombus not yet described in literature and this makes our case worth mentioning.